Low-Cost Solar Pump Irrigation System for Irrigated Rice Production (Bangladesh Rice Journal, 2023)
Irrigation pumps operated by diesel and electricity are commonly used for irrigated rice cultivation, but fuel cost expansion and doubtful accessibility of power hampers the continuous irrigation. A solar pump would be an alternative option for irrigation to contribute in expanding rice production and food security to the growing population. Field experiments were conducted at Bangladesh Rice Research Institute, Gazipur, farm during Boro season from January May in 2015, 2016 and 2017, respectively to determine the economic feasibility of a low cost 1.5 Horsepower (hp ) capacity solar irrigation pump for rice cultivation. BRRI dhan63 was tested under four irrigation treatments as flood irrigation (continuous standing water at 7 cm depth above the soil surface), 3 cm irrigation at saturation level, 3 cm irrigation in AWD (alternate wetting and drying) practice, and 5 cm irrigation in AWD practice. The CROPWAT 8.0 model was used to ascertain crop water requirement (CWR) and irrigation requirement of each rice growth phase in each year using weather data. In 3 cm irrigation in AWD practice, about 1.0 ha of paddy field can be irrigated with the 1.5 hp solar pump without any or a few water deficits in reproductive and ripening phases. In both years, rice yield did not differ among the irrigation treatments. The benefit-cost ratio was 1.09, 1.18 and 1.02 for Aman, mustard and Boro season respectively. A 1.5 hp solar pump is the best feasible when it is used yearround for three or more crops. Although solar pump irrigation system involved higher initial cost, it was found economically sound and environment friendly. Thus, proper policy support is required to encourage solar power utilization for irrigation.Bangladesh Rice J. 25 (2) : 1-10, 2021